1987
DOI: 10.1104/pp.83.4.982
|View full text |Cite
|
Sign up to set email alerts
|

Partial Purification of Digitonin-Solubilized β-Glucan Synthase from Red Beet Root

Abstract: An enriched glucan synthase fraction was obtained from red beet root microsomes by sequential extraction with the detergents 3-1(3-cholamidopropyl)dimethylammoniol-l-propanesulfonate and digitonin. The digitonin suspension was centrifuged on a glycerol gradient, where a glucan synthase peak with a specific activity of 30-to 40-fold over microsomes was recovered. Most protein contaminants were found in the gradient pellet. The glucan synthase-containing fraction was largely free of plasma membrane and tonoplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
(27 reference statements)
1
13
0
Order By: Relevance
“…This phenomenon is due to nonspecific precipitation of the enzyme as the combined result of a decrease in detergent levels and an increase in divalent cation concentration. It has already been shown that divalent cations inhibit CS solubilization (8,23) and that the enzyme solubilized with digitonin sediments faster in glycerol gradients containing cations than it does in the presence of chelators (12). Here we show that CS solubilized in CHAPS and enriched by product entrapment is also prone to cation-induced aggregation (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…This phenomenon is due to nonspecific precipitation of the enzyme as the combined result of a decrease in detergent levels and an increase in divalent cation concentration. It has already been shown that divalent cations inhibit CS solubilization (8,23) and that the enzyme solubilized with digitonin sediments faster in glycerol gradients containing cations than it does in the presence of chelators (12). Here we show that CS solubilized in CHAPS and enriched by product entrapment is also prone to cation-induced aggregation (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…At 4"C, the microsomal enzyme maintained full activity. Solubilized enzyme stored at -80'C began to show a decline in activity after 8 h and at 4"C after 4 h. Thus, solubilized carrot glucan synthase is considerably less stable than beet (11,12,28).…”
Section: Stability Of the Solubilized Enzymementioning
confidence: 98%
“…It has been shown that glucan synthases are large protein complexes (>450 kD) and that several protein subunits ranging from 18 to 115 kD might be involved in glucan synthesis (Delmer, 1987;Eiberger and Wasserman, 1987; -uv Read and Delmer, 1987;Bulone et al, 1990;Lin et al, 1990). Efforts have been directed at defining the relationship between the individual components in various synthase preparations and, in particular, at identifying which polypeptides might participate in (1-»3)-and/or (1-»4)-/3-glucan synthesis.…”
Section: Discussionmentioning
confidence: 99%